(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Field experiments were conducted at the Teaching and Research Farm of the Faculty of Agriculture to evaluate the genetic variability, heritability, and genetic advance of some selected agronomic traits of fifteen (15) newly developed promising cowpea genotypes. Cowpea, a crucial legume crop, is widely grown in arid and semi-arid regions for its early maturity, drought and heat tolerance, and nutritional value. This study assessed genetic variation among newly developed cowpea genotypes and determined agronomic traits’ heritability and genetic advance. Genetic variability is crucial for improved varieties, while heritability measures phenotypic variation caused by genetic differences. Genetic advancement measures the potential increase in trait value through selection in breeding populations. The study reveals significant genetic variation among 15 cowpea genotypes, indicating a wide range of agronomic traits for selective breeding. Four traits-leaf length, leaf weight, days until first flowering, and 50% flowering-demonstrated high heritability and genetic advancements. These traits may be promising for targeted breeding efforts because they respond well to selection pressure and can be improved through phenotypic selection. Cowpea varieties with improved performance, yield potential, and adaptability to varying environmental conditions can be developed by focusing on these traits, contributing to food security and agricultural sustainability.